Integration of Biofloc and Ozone Nanobubbles for Enhanced Pathogen Control in Prenursery of Pacific White Shrimp (Penaeus vannamei) - Qinlang Liang; Yazhi Luan; Zhengwen Wang; Jiangbo Niu; Yasong Li; Hua Tang; Zengting Li; Songming Zhu; Gang Liu (Fishes, 2025)
This study investigates the synergistic effects of integrating ozone nanobubbles (generated via a pure oxygen-fed reactor with nanobubble-diffusing air stones) and biofloc technology (BFT) on water quality optimization, pathogenic load reduction, and growth performance enhancement in Pacific white shrimp (Penaeus vannamei) prenursery aquaculture systems. Four treatments were tested: a clear water control (CW), ozonated clear water (CW + O), biofloc (FLOC), and biofloc with ozone (FLOC + O). The FLOC + O group significantly improved water quality, reducing total ammonia nitrogen (TAN) by 61%, nitrite nitrogen (NO2−-N) by 78% compared to CW, and total suspended solids (TSS) by 21% compared to FLOC (p = 0.0015). Ozone application (maintained above 0.3 mg/L, 15 min/day) demonstrated robust pathogen suppression, achieving a sharp reduction in Muscle Necrosis Virus (MNV), a 99.5% inhibition of Vibrio spp. (from 228,885 to 107 CFU/mL), and the clearance of Epistylis spp., as determined via optical microscope. These enhancements directly translated to superior biological outcomes, with the FLOC + O group exhibiting an 82% survival rate (vs. 40% in CW) and 13% higher final body weight (11.65 mg vs. 10.32 mg in CW). The integration of ozone and BFT also accelerated larval development and improved the Zoea II to Mysis I metamorphosis success rate. By maintaining stable microbial communities and reducing organic waste, the combined system lowered the water exchange frequency by 40% and eliminated the need for prophylactic antibiotics. These results demonstrate that ozone–BFT integration effectively addresses key challenges in shrimp prenursery—enhancing disease resistance, optimizing water conditions, and improving growth efficiency. The technology offers a sustainable strategy for the intensive prenursery of Pacific white shrimp, balancing ecological resilience with production scalability.